Household‐level predictors of maternal mental health and systemic inflammation among infants in Mwanza, Tanzania. Issue 4 (23rd November 2015) - Decaro, Jason A.; Manyama, Mange; Wilson, Warren
Abstract : Objectives: Household conditions and culturally/socially variable childcare practices influence priming of the inflammatory response during infancy. Maternal mental health may partially mediate that effect. Among mother–infant dyads in Mwanza, Tanzania, we hypothesized that poorer maternal mental health would be associated with adverse household ecology, lower social capital, and greater inflammation among infants under the age of one; and that mental health would mediate any effects of household ecology/social capital on inflammation. Methods: We collected dried blood spots from mother–infant dyads ( N  = 88) at health centers near Mwanza, Tanzania. To assess household ecology and social capital, we conducted interviews with mothers using the Household Food Insecurity Access Scale, the MacArthur Subjective Social Status Scale, and a household wealth inventory. We employed the Hopkins Symptom Checklist to assess maternal mental health. A high‐sensitivity C‐reactive protein (CRP) assay was used to quantify inflammation. Results: Severe food insecurity (OR: 5.16), lower subjective social status ( r = −0.32), and lower household wealth ( r  = −0.26) were associated with high symptoms of maternal depression. Lower household wealth ( r = −0.21) and severe food insecurity (OR: 2.52) were associated with high anxiety. High depression symptoms (OR: 2.56) and severe food insecurity (OR: 2.77) each were associated with greater‐than‐median infant CRP. However, mediation was not supported. Conclusions: Maternal mental health should be considered alongside nutritional status, pathogen exposure, and education as a potential driver of very early innate immune system development. Proximal mechanisms warrant further investigation. Am. J. Hum. Biol. 28:461–470, 2016. © 2015 Wiley Periodicals, Inc.